Intergovernmental Relations Pattern of Smart Kampung Program in Banyuwangi - Rahmatul Ilmi, Maulida; Suryawati, Dina; Indriastuti, Suyani (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
The Smart Kampung Programme in Banyuwangi Regency is an innovative initiative that aims to improve the welfare of village communities through the use of information and communication technology. The programme covers various aspects, such as public services, education, health, and economic empowerment. In its implementation, the programme involves various levels of government, ranging from the village government to the district government, as well as support from the central government. This article aims to analyse intergovernmental relations in the implementation of the Smart Kampung Programme in Banyuwangi Regency. The main focus is on how coordination, collaboration and synergy between different levels of government play a role in the success of this programme. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with government officials at various levels, field observations, and analysis of official documents. The intergovernmental relationship in the Smart Kampung Programme in Banyuwangi Regency shows top down and botton up cooperation patterns as well as the importance of coordination, collaboration, and synergy to achieve programme success. This success cannot be separated from the active role of each level of government and the adaptation of the programme according to the local conditions needed. This programme can serve as a model for other regions in implementing similar initiatives.